2020
DOI: 10.1002/dta.2789
|View full text |Cite
|
Sign up to set email alerts
|

Return of the lysergamides. Part VI: Analytical and behavioural characterization of 1‐cyclopropanoyl‐d‐lysergic acid diethylamide (1CP‐LSD)

Abstract: Lysergic acid diethylamide (LSD) is a prototypical serotonergic psychedelic drug and the subject of many clinical investigations. In recent years, a range of lysergamides has emerged with the production of some being inspired by the existing scientific literature. Others, for example various 1‐acyl substituted lysergamides, did not exist before their appearance as research chemicals. 1‐Cylopropanoyl‐LSD (1CP‐LSD) has recently emerged as a new addition to the group of lysergamide‐based designer drugs and is bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 22 publications
(66 citation statements)
references
References 33 publications
7
59
0
Order By: Relevance
“…ESI‐QTOF‐MS/MS and ESI single quadrupole mass spectra subjected to in‐source collision‐induced dissociation are shown in Figure 3; proposed product ions involving high‐resolution measurements are summarized in the Supporting Information based on the principles discussed in previous reports on related lysergamides 8–13 . A visual comparison of mass spectral data (Figure 3) revealed that the product ions formed were comparable to the ions observed during LSZ analysis, 9 although some variations were noted in the relative abundance of some of the product ions.…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…ESI‐QTOF‐MS/MS and ESI single quadrupole mass spectra subjected to in‐source collision‐induced dissociation are shown in Figure 3; proposed product ions involving high‐resolution measurements are summarized in the Supporting Information based on the principles discussed in previous reports on related lysergamides 8–13 . A visual comparison of mass spectral data (Figure 3) revealed that the product ions formed were comparable to the ions observed during LSZ analysis, 9 although some variations were noted in the relative abundance of some of the product ions.…”
Section: Resultsmentioning
confidence: 72%
“…The electron ionization (EI) mass spectrum of ECPLA is depicted in Figure 2B) which was not detected to that extent in related lysergamides investigated previously under the conditions used. [8][9][10][11][12][13] Whilst the relative abundance of the ion was around 15% for LSZ, (Figure 3) revealed that the product ions formed were comparable to the ions observed during LSZ analysis, 9 although some variations were noted in the relative abundance of some of the product ions. For example, ions typically observed here and other related lysergamides [8][9][10][11][12][13] included ions at m/z 251, 223, 208, 197, 180, and 140.…”
Section: Gas Chromatography-mass Spectrometry (Gc-ms)mentioning
confidence: 77%
See 3 more Smart Citations